2006
DOI: 10.1111/j.1442-9071.2006.01147.x
|View full text |Cite
|
Sign up to set email alerts
|

Limbal stem cells: the search for a marker

Abstract: The corneal epithelium is a self-renewing tissue and must, by definition, have a resident basal cell population necessary for homeostasis and wound healing. There is a substantial body of evidence, both experimental and clinical, pointing to the basal cells of the limbus as the location of corneal epithelial stem cells. However, in the absence of a definitive marker of limbal stem cells, the evidence remains largely circumstantial. Many markers such as p63 and integrin alpha9 are preferentially localized to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
1
2

Year Published

2008
2008
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 106 publications
(79 citation statements)
references
References 70 publications
4
72
1
2
Order By: Relevance
“…Positive LESC markers include cytokeratins Ck15, Ck14, Ck19, NGF receptor TrkA, vimentin, integrins a6, a9, b1, and b4. Negative markers are involucrin, connexins 43, and 50, along with cytokeratins Ck3 and Ck12 [reviewed in (56)(57)(58)(59)(60)(61)(62)]. A recent study has shown that integrin a9 positive cells are located adjacent to label retaining limbal basal cells, which in turn are negative for integrin a9.…”
Section: Molecular Markers Of Lescsmentioning
confidence: 99%
“…Positive LESC markers include cytokeratins Ck15, Ck14, Ck19, NGF receptor TrkA, vimentin, integrins a6, a9, b1, and b4. Negative markers are involucrin, connexins 43, and 50, along with cytokeratins Ck3 and Ck12 [reviewed in (56)(57)(58)(59)(60)(61)(62)]. A recent study has shown that integrin a9 positive cells are located adjacent to label retaining limbal basal cells, which in turn are negative for integrin a9.…”
Section: Molecular Markers Of Lescsmentioning
confidence: 99%
“…Experimental and clinical evidence pointing to the limbus as the source of corneal epithelial stem cells is compelling [19][20][21][22]. Relatively undifferentiated and slow-cycling epithelial cells have been found in the limbal basal layer but not in the central cornea [12][13][14].…”
Section: Location Of Human Corneal Stem Cellsmentioning
confidence: 99%
“…The limbus harbours the stem cells of the corneal epithelium [10,[12][13][14][15][16][17][18]. Limbal stem cell identification and molecular characterization have been reviewed [19,20], but not in relation to tissue regeneration. We address here some of the issues related to limbal stem cell-mediated regenerative medicine.…”
Section: G Pellegrini Et Almentioning
confidence: 99%
See 1 more Smart Citation
“…However, an open issue in corneal regeneration is the lack of a dependable surface marker of the limbal stem cell population (41). The results of this work show that CD38 and CD157 mark subsets of human corneal epithelial cells.…”
Section: Discussionmentioning
confidence: 53%